Peran Ganda Jurnalis dan Penyimpangan Kode Etik Jurnalistik - Agung Priyo Wicaksono (Institut Seni Indonesia Yogyakarta, 2023)
ABSTRAKPenyebab Peran Ganda Jurnalis Dan Penyimpangan Kode Etik Jurnalistik. Pesatnya kemajuan teknologi dan komunikasi berpengaruh besar bagi kematian media konvensional. Keadaan ini memaksa media untuk membebani jurnalis dengan peran ganda agar dapat menghidupi media. Penelitian ini bertujuan mengetahui penyebab peran ganda di kalangan jurnalis. Penelitian kualitatif dilakukan dengan pendekatan fenomenologi. Data dalam penelitian diperoleh melalui Focus Group Discussion dan wawancara mendalam dengan tujuh orang jurnalis dari berbagai media di Yogyakarta. Hasil penelitian menunjukkan tiga poin penting. Pertama, peran ganda terjadi karena persaingan media yang begitu ketat. Persaingan media membuat media konvensional kehilangan kue iklan sehingga memaksa perusahaan untuk memberikan peran ganda kepada jurnalis. Kedua, peran ganda terjadi karena upah rendah yang diperoleh jurnalis. Keadaan ini membuat jurnalis terpaksa menjalankan praktik peran ganda guna mendapatkan upah yang sesuai. Ketiga, peran ganda terjadi karena pola rekrutmen jurnalis yang berorientasi pada pasar bukan pada kompetensi jurnalis. Dual Role of Journalists and Violation of Journalism Ethics. The rapid advances in technology and communication have had a major effect on the death of conventional media. This situation forces the media to burden the dual role for journalists in order to support the media. This study aims to find out the causes of dual roles among journalists. This qualitative research was conducted using a phenomenological approach. The data in this study were obtained through in-depth interviews and Focus Group Discussion with seven journalists from various media in Yogyakarta. The research results showed three important points. First, the dual role occurs because the media competition is so intense. Media competition makes conventional media lose their hot cakes of advertising, forcing companies to give dual roles to journalists. Second, the dual role occurs because of the low wages earned by journalists. This situation forces journalists to practice multiple roles in order to get the appropriate wages. Third, the dual role occurs due to the journalist recruitment pattern which is market oriented, not journalist competence. The results of the research show that the tendency to deviate from the journalism ethics is due to the coercion of media companies for journalists to earn income by becoming advertisers. Intervention by media companies is not justified when journalists perform their professional duties. Similarly, low wages make journalists try to earn additional income by becoming advertisement seekers, which is not in line with the journalist's main duties. In addition, the recruitment of journalists from the start does not focus on professional competence but rather on journalists who are willing to become advertisement seekers, not looking for information.